Human Leukocyte Antigen Association Study Reveals DRB1*04:02 Effects Additional to DRB1*07:01 in Anti-LGI1 Encephalitis. Issue 2 (3rd March 2022) - Peris Sempere, Vicente; Muñiz-Castrillo, Sergio; Ambati, Aditya; Binks, Sophie; Pinto, Anne-Laurie; Rogemond, Veronique; Pittock, Sean J.; Dubey, Divyanshu; Geschwind, Michael D.; Gelfand, Jeffrey Marc; Dilwali, Sonam; Lee, Soon-Tae; et al.
Abstract : Background and Objectives: To study human leukocyte antigen (HLA) allele associations in anti-leucine–rich glioma-inactivated 1 (LGI1) encephalitis. Methods: A multiethnic cohort of 269 patients with anti-LGI1 encephalitis and 1, 359 controls was included. Four-digit HLA sequencing and genome wide association single-nucleotide polymorphism typing imputation (0.99 concordance) were used for HLA typing. Significance of primary and secondary associations was tested using χ 2, Fisher exact tests, or logistic regression with the control of population stratification covariates when applicable. Results: DRB1*07:01 and DQA1*02:01, 2 alleles in strong linkage disequilibrium, were associated with the disease (90% vs 24%, OR = 27.8, p < 10e −50 ) across ethnicity independent of variation at DRB3 and DQB1, 2 flanking HLA loci. DRB1*07:01 homozygosity was associated with a doubling of risk (OR = 2.1, p = 0.010), suggesting causality. DRB1*07:01 negative subjects were younger ( p = 0.003) and more frequently female ( p = 0.015). Three patients with malignant thymomas did not carry DRB1*07:01, whereas patients with other tumors had high DRB1*07:01 frequency, suggesting that the presence of tumors other than thymomas may be coincidental and not causal. In both DRB1*07:01 heterozygous individuals and DRB1*07:01 negative subjects, DRB1*04:02 was associated with anti-LGI1 encephalitis, indicating an independent effect of this allele (OR = 6.85, p = 4.57 × 10 −6 and OR = 8.93, p = 2.50 × 10 −3, respectively). DRB1*04:02 was also independently associated with younger age at onset (β = −6.68, p = 9.78 × 10 −3 ). Major histocompatibility complex peptide-binding predictions using LGI1-derived peptides revealed divergent binding propensities for DRB1*04:02 and DRB1*07:01 alleles, suggesting independent pathogenic mechanisms. Discussion: In addition to the established primary DRB1*07:01 association in anti-LGI1 encephalitis, we observe a secondary effect of DRB1*04:02 with lower age at onset. Our study provides evidence for secondary effects within HLA locus that correlate with clinical phenotypes in anti-LGI1 encephalitis.